2004
DOI: 10.1097/00001756-200404290-00024
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive MMN relative to sound types in adults with intellectual disability

Abstract: The effect of stimulus characteristics (vowel vs pure tone) upon mismatch negativity (MMN) was compared between adults with intellectual disability and healthy controls. Either vowels (synthesized vowels /e/ and /o/) or pure tones (1940 and 851 Hz corresponding to the F2 frequencies of /e/ and /o/, respectively) were presented using an oddball procedure. Both groups showed identical results in latency (vowel MMN>pure tone MMN) and less amplitudes for vowels. However, the disabled group demonstrated amplitude a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Ikeda and colleagues conducted three studies investigating MMN in adult subjects with ID, using a passive oddball paradigm with synthetic vowels and pure tones. An attenuated MMN amplitude to both kinds of stimuli was found in patients with ID in all three studies (Ikeda et al, 2000, 2004, 2009), whereas greater MMN latencies in ID were only observed in the first study (Ikeda et al, 2000). Holopainen's group also found attenuated MMN amplitudes in a passive oddball paradigm at the individual maximal electrode for children with ID and children with dysphasia in comparison to a group with healthy control children, but no differences in latency (Holopainen et al, 1998).…”
Section: Mismatch Negativity—mmnmentioning
confidence: 87%
“…Ikeda and colleagues conducted three studies investigating MMN in adult subjects with ID, using a passive oddball paradigm with synthetic vowels and pure tones. An attenuated MMN amplitude to both kinds of stimuli was found in patients with ID in all three studies (Ikeda et al, 2000, 2004, 2009), whereas greater MMN latencies in ID were only observed in the first study (Ikeda et al, 2000). Holopainen's group also found attenuated MMN amplitudes in a passive oddball paradigm at the individual maximal electrode for children with ID and children with dysphasia in comparison to a group with healthy control children, but no differences in latency (Holopainen et al, 1998).…”
Section: Mismatch Negativity—mmnmentioning
confidence: 87%
“…Furthermore, because this research did not include a control sample of adolescents with intellectual impairments or language disorders without autism, we cannot make any firm conclusions that our findings are specific to individuals with ASD. In fact, given similar findings of auditory processing differences in individuals with developmental language disorders (Bishop & McArthur, 2004; Kwok, Joanisse, Archibald, & Cardy, 2018) and intellectual impairments (Ikeda et al, 2004, 2009; Jaušovec & Jaušovec, 2000; Orekhova et al, 2008; Rotschafer & Razak, 2014), and our hypothesis that distortions in simple processing of sensory inputs may have cascading impacts on generalized cognition, we do not necessarily expect our findings to be specific to autistic individuals. Non‐autistics who are impacted by similar difficulties with low‐level processing may also show similar results.…”
Section: Research Limitationsmentioning
confidence: 83%
“…Because neuroimaging research is quite challenging to conduct on individuals with intellectual impairments, minimal research has been conducted on them to examine their neural response to sounds. In the limited research that has occurred, researchers have found individuals with profound intellectual impairments, with and without autism, display differences in the amplitude and latency of their early neural responses to sounds (Ikeda et al, 2004(Ikeda et al, , 2009Jaušovec & Jaušovec, 2000;Orekhova et al, 2008;Rotschafer & Razak, 2014). Further research is needed to characterize neural response to sounds in those with profound intellectual impairments, with or without accompanying autism.…”
Section: Introductionmentioning
confidence: 99%